DEVELOPMENT OF DISCOVERY LEARNING-BASED MATHEMATICS LEARNING MEDIA ACCOMPANIED BY CROSSWORD PUZZLES OF INTEGER MATERIAL - Lidia Marsela Putri; Nego Linuhung; Ira Vahlia (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
This study aims to develop android-based mathematics learning media using a discovery learning approach and crossword puzzle games on the topic of integers for SMP Negeri 4 Metro. The development model used is ADDIE, which includes the stages of analysis, design, development, implementation, and evaluation. The analysis stage was conducted through interviews with educators and student questionnaires to identify media needs. In the design stage, interactive media combining discovery learning and games was developed. The development stage included validation by subject matter and media experts, resulting in a very good score of 86.5%. Implementation showed that the media was practical to use, with a 93% success rate, and evaluation was conducted continuously to improve the product. The results of the study indicate that the learning media are highly valid and practical for use in teaching integers. It implies that this media can be an innovative solution to enhance student engagement and the effectiveness of mathematics learning, and it has the potential to be further developed for other topics and educational levels to create more interactive and flexible learning.